Real-world particle and NOx emissions from hybrid electric vehicles under cold weather conditions. (1st October 2021) - Li, Chengguo; Swanson, Jacob; Pham, Liem; Hu, Shaohua; Hu, Shishan; Mikailian, Gary; Jung, Heejung S.
Abstract: Hybrid electric vehicle (HEV) technology is critical to reduce the impact of the internal combustion engines on air pollution and greenhouse gases. HEVs have an advantage in market penetration due to their lower cost and higher driving range compared to battery electric vehicles (BEVs). On the other hand, HEVs use an internal combustion engine and still emit air pollutants. It is hypothesized that HEV performance is impacted by the weather conditions as a result of many factors. It was beyond the scope of this work to systematically evaluate all factors so instead we measured emissions from two vehicles driving city and highway routes in Minneapolis, Minnesota in the winter (−5 °C) and looked for major differences in emissions relative to each vehicle and relative to results that would be obtained from a chassis dynamometer in a controlled laboratory setting at a higher temperature approximately 20 °C). The study then looked to associate differences in emissions with the prevailing conditions to gain new insights. Emissions of interest included the total particle number (TPN), solid particle number (SPN), particulate matter mass (PM), and NOx. One key difference in vehicle engine technology was PFI (port fuel injection) versus GDI (gasoline direct injection). We found the frequency at which the Prius hybrid engine reignited was much higher than the Sonata for city and highway driving, although for both vehicles the catalyst temperature remained high and appeared to be unaffected by the reignitions, despite the cold weather. For most conditions, the Prius emitted more NOx but fewer particles than the Sonata. In some cases, NOx and particle emissions exceeded the most comparable laboratory-based emissions standards. Graphical abstract: Image 1 Highlights: PM and NOx emissions increased under cold weather conditions. Re-ignition events, hybridization ratio, and power distribution strategy may have affected emissions. Re-ignition events were much more frequent and varied from vehicle to vehicle.